2007
DOI: 10.18806/tesl.v25i1.109
|View full text |Cite
|
Sign up to set email alerts
|

Revision in Second Language Writing: What Teachers Need to Know

Abstract: Revising is an essential component of skilled writing. Yet it seems to play a limited role in the writing of many novice second-language (L2) writers. These writers may find it easier to generate ideas than to revise what they have written in relation to task requirements and their writing goals and audience. Consequently, many fail to revise frequently, extensively, or skilfully. This article reviews research on revision in L2 writing in an attempt to understand how and what skilled and unskilled L2 writers r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 35 publications
3
46
0
Order By: Relevance
“…This is in agreement with what Yu-Ling and Shih-Guey (2001), and Victori (1999) found. This is also in tandem with Barkaoui (2007) who explains that less-skilled SL writers do not distinguish between editing and revising. Skilled writers, on the contrary, regarded revision as a strategy which reshapes their works.…”
Section: Discussionsupporting
confidence: 62%
“…This is in agreement with what Yu-Ling and Shih-Guey (2001), and Victori (1999) found. This is also in tandem with Barkaoui (2007) who explains that less-skilled SL writers do not distinguish between editing and revising. Skilled writers, on the contrary, regarded revision as a strategy which reshapes their works.…”
Section: Discussionsupporting
confidence: 62%
“…Certainly there is a general scholarly consensus regarding the importance of revision in the writing process: as Barkaoui (2007) notes after citing numerous sources going back decades (Faigley & Witte, 1981;Sommers, 1980;Witte, 1985;Zamel, 1982), "good writers seem to revise at all stages of the writing process as they generate, reevaluate, reformulate, and refine their writing goals" (p. 81). Despite this widespread recognition of the importance of revision, considerable variation in (Whitney et al, 2008) and even ambiguity about (Witte, 2013) the teaching of revision remains.…”
Section: Visions Of Revision Uncertainties and Opportunitiesmentioning
confidence: 99%
“…In previous research on the writing process of skilled and unskilled students (e.g, Bosher, 1998;Nunan, 1991;Roca de Larios, Murphy, & Manchon, 1999;Zamel, 1983), it has been concluded that skilled L2 writers tend to spend more time to plan, revise and do writing tasks in the most effective way . Also, their main concerns were in the discourse levels like global content, organization, topic sentences, coherence and unity (Barkaoui, 2007;Nunan, 1991;Tsai, 2009). …”
Section: The Effectiveness Of Topical Structure Analysis Instructionmentioning
confidence: 99%